2023
DOI: 10.3102/00346543231178830
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Writing Relations Are Not Uniform: They Differ by the Linguistic Grain Size, Developmental Phase, and Measurement

Abstract: We conducted a meta-analysis to investigate reading-writing relations. Beyond the overall relation, we systematically investigated moderation of the relation as a function of linguistic grain size (word reading and spelling versus reading comprehension and written composition), measurement of reading comprehension (e.g., multiple choice, open-ended, cloze), and written composition (e.g., writing quality, writing productivity, writing fluency, writing syntax), and developmental phase of reading and writing (gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Although reading and writing have distinct characteristics, they are also related. A recent meta-analysis of a large body of literature showed that students who are strong in word reading tend to be strong in spelling and vice versa, and similarly, students who are strong in reading comprehension tend to be strong in written composition and vice versa (Kim, Wolters, & Lee, 2024). This is because reading and writing are built on largely shared systems and skills (Fitzgerald & Shanahan, 2000;Kim, 2020aKim, , 2022.…”
Section: How Are Reading and Writing Related?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although reading and writing have distinct characteristics, they are also related. A recent meta-analysis of a large body of literature showed that students who are strong in word reading tend to be strong in spelling and vice versa, and similarly, students who are strong in reading comprehension tend to be strong in written composition and vice versa (Kim, Wolters, & Lee, 2024). This is because reading and writing are built on largely shared systems and skills (Fitzgerald & Shanahan, 2000;Kim, 2020aKim, , 2022.…”
Section: How Are Reading and Writing Related?mentioning
confidence: 99%
“…The need for making reading-writing connections explicit is particularly important for reading comprehension and written composition compared to word reading and spelling because the extent to which comprehension and composition draw on the skills and knowledge differ, and therefore, their relation is not as strong as for word reading and spelling (Kim, 2020a(Kim, , 2022Kim, Wolters, & Lee, 2024). This means that students are less likely to transfer skills learned in comprehension to composition or vice versa.…”
Section: Making Reading-writing Connections Visiblementioning
confidence: 99%